SOSIALISASI PENINGKATAN INOVASI PRODUK DALAM MENGHADAPI TANTANGAN PEMASARAN GLOBAL UNTUK MENINGKATKAN PENDAPATAN MASYARAKAT PADA KELOMPOK PETANI AREN DI DESA PUSUK LESTARI KECAMATAN BATU LAYAR LOMBOK BARAT - Rispawati, Dewi (LP2M STP Mataram, 2024)
This community service is entitled “Socialization of Increasing Product Innovation in Facing Global Marketing Challenges to Increase Community Income in Aren Farmers Groups in Pusuk Lestari Village, Batu Layar District West Lombok”, which aims to increase Product Innovation in facing Global Marketing challenges to increase community income in Pusuk Lestari Village. This community service uses a method that is implemented in 3 (three) stages of activity, namely: 1) Preparation, 2) Socialization, and 3) Activity Implementation. The results of community service activities show that the community in Pusuk Lestari Village, Batu Layar District, West Lombok is very enthusiastic and has understood about product innovation after being socialized, so that it can be improved in the future to make product innovations that are more varied from the products previously produced. Product innovation carried out in the future is expected to increase community income because it has a selling value from the innovation products produced and can increase the income of community members who are entrepreneurs in Pusuk Lestari Village, Batu Layar District, West Lombok